Termografia infravermelho na estimativa de conforto térmico de frangos de corte - Nascimento, Guilherme R. Do; Nääs, Irenilza A.; Baracho, Marta S.; Pereira, Danilo Florentino [UNESP]; Neves, Diego P. (Departamento de Engenharia Agrícola - UFCG, 2014)
Poultry facilities must provide an environment that ensures thermal comfort allowing the animal to express its genetic potential for production; and new tools are being applied to measure the thermal comfort, especially thermal cameras. The objective of this study was to evaluate the association of the surface temperature of the birds with those from the facilities, and estimate the sensible heat transfer. For this, the thermal conditions of rearing in two aviaries with different ventilation systems, during the period of March to April 2011 were recorded. The aviaries were divided into six quadrants for the registration of surface temperatures obtained using an infrared thermal camera. In each quadrant the ambient temperature, relative humidity and wind velocity during the obtention of images were also recorded. It was observed that the surface temperatures of birds are associated with the surface temperature of the rearing facilities (side curtains, roof and litter). In aviary with negative pressure higher wind speeds compared to the conventional one were recorded and; therefore, allowed a higher sensible heat transfer by birds, suggesting that this provided better conditions for thermal comfort.

As instalações avícolas devem assegurar um ambiente de conforto térmico que proporcione ao animal expressar todo o seu potencial genético para produção motivo pelo qual novas ferramentas estão sendo aplicadas para medir o conforto térmico animal destacando-se as câmeras termográficas. Neste trabalho objetivou-se avaliar a associação da temperatura superficial das aves com as das instalações e estimar a transferência de calor sensível. Para isto foram registradas as condições térmicas de alojamento em dois aviários com sistemas de ventilação distintos, no período de março a abril de 2011. Os aviários foram divididos em seis quadrantes para a coleta das temperaturas superficiais obtidas através de uma câmera termográfica infravermelho. Em cada quadrante também foram registradas temperatura ambiente, umidade relativa e velocidade do ar durante as coletas das imagens. Constatou-se que as temperaturas superficiais das aves estão associadas à temperatura superficial da instalação (cortinas laterais, forro e cama). No aviário com ventilação negativa foram registradas maiores velocidades do ar em relação ao convencional razão pela qual possibilitou a maior transferência de calor sensível pelas aves, sugerindo melhores condições de conforto térmico.
Infrared thermography in the estimation of thermal comfort of broilers
Keywords: bem-estar; temperatura superficial; termorregulação; welfare; surface temperature; thermoregulation